Case Report: Comparison different response after neoadjuvant chemotherapy of the breast with cell-in-cell—report of two cases - Zhan, Danhong; Li, Zhikang; Yu, Kaiting; Wang, Chenxi; Sun, Qiang; Wang, Ruizhi; He, Meifang (Frontiers in Medicine, 2026)
Neoadjuvant chemotherapy (NACT) is commonly applied in human epidermal growth factor receptor 2 (HER2)-positive breast cancer to reduce tumor size and increase the likelihood of breast-conserving surgery. However, predictive markers of response remain limited. We report two cases of HER2-positive breast cancer with divergent responses to NACT, highlighting the dynamics of cell-in-cell structures (CICs). Both patients initially presented with palpable breast masses and biopsy-confirmed HER2-positive invasive carcinoma with frequent CICs. After NACT, one patient achieved a favorable pathological response, accompanied by a reduction in CICs frequency. In contrast, the other patient showed limited response, with persistent complex CICs, which led to an adjustment of the adjuvant regimen. These observations suggest that dynamic cell-in-cell (CIC) patterns may reflect heterogeneous tumor responses to NACT, providing insights for individualized treatment planning.